Assessment of precision in growth inhibition assay (GIA) using human anti-PfRH5 antibodies - Miura, K; Diouf, A; Fay, MP; Barrett, JR; Payne, RO; Olotu, AI; Minassian, AM; Silk, SE; Draper, SJ; Long, CA (BioMed Central, 2023)
Background For blood-stage malaria vaccine development, the in vitro growth inhibition assay (GIA) has been widely used to evaluate functionality of vaccine-induced antibodies (Ab), and Plasmodium falciparum reticulocyte-binding protein homolog 5 (RH5) is a leading blood-stage antigen. However, precision, also called “error of assay (EoA)”, in GIA readouts and the source of EoA has not been evaluated systematically.